2022
DOI: 10.1007/s00445-022-01584-2
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Popocatépetl’s activity by regional and worldwide earthquakes

Abstract: Volcanoes switching from quiescence to eruption shortly after catastrophic earthquakes have raised interest for volcanic triggering and the influence of earthquakes on volcanic activity. Its influence on already active systems and especially at open-vent volcanoes is more difficult to apprehend. A number of recent observations suggest an influence of tectonic earthquakes on Popocatépetl’s activity, the importance of which remains unknown. To further investigate this, we introduce an index, based on the near-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 157 publications
1
7
0
Order By: Relevance
“…Following a relatively intense extrusive activity during September-December 2018, with the succession of the dome emplacement-destruction cycles #80 and #81 (CENAPRED daily reports; Caballero Jimenez et al, 2019), January 2019 is marked by a powerful explosion on day 22, apparently without a dome occupying the crater. Such explosions are rare, but they became more frequent following the earthquakes of 2017 (Boulesteix et al, 2022). A crater overflight was operated on day 27, which confirmed that the crater was still empty and that the conduit was permeable.…”
Section: Popocatépetl Volcano and Measurement Sitementioning
confidence: 84%
“…Following a relatively intense extrusive activity during September-December 2018, with the succession of the dome emplacement-destruction cycles #80 and #81 (CENAPRED daily reports; Caballero Jimenez et al, 2019), January 2019 is marked by a powerful explosion on day 22, apparently without a dome occupying the crater. Such explosions are rare, but they became more frequent following the earthquakes of 2017 (Boulesteix et al, 2022). A crater overflight was operated on day 27, which confirmed that the crater was still empty and that the conduit was permeable.…”
Section: Popocatépetl Volcano and Measurement Sitementioning
confidence: 84%
“…Popocatépetl has experienced since its reactivation in 1994 32 successive episodes of lava dome construction and destruction 33 , 34 . The morphological characteristics of the domes fall into the broad category of low lava domes 3 , typically pancake-shaped and affected by subsidence and dome-destruction explosive processes following their emplacement 34 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies show that seismic events can be frequently used as precursors to volcanic processes [13][14][15]. Boulesteix et al [16] noted that volcanoes very often erupt, i.e., change from a passive phase to an active phase, soon after strong earthquakes. Many authors refer to catastrophic earthquakes as a seismic trigger for volcanism [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The Popocatépetl volcano (latitude: 19.023 N, longitude: −98.622 E, elevation: 5465 m), located in the platform part of Mexico and one of the most active volcanoes in North America, was chosen as an object for studying these processes. A number of researchers [16] have suggested that the activity of Popocatepetl is influenced by tectonic activity. These authors introduced an index based on the near-field concept to assess the influence of seismicity on volcanic activity [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation